Responses of physical education students to teaching assistance program - Bayu Insanistyo; Yahya Eko Nopiyanto; Ipa Sari Kardi; Ibrahim Ibrahim (Universitas Riau, 2023)
(English)Teaching assistance provides opportunities for students to develop their potential and interest in teaching in educational units in Indonesia. However, the implementation in the field of the teaching assistance program cannot be separated from various obstacles and various responses from students. This research aims to reveal the response of physical education students to the teaching assistance program in 2023. This research uses quantitative descriptive methods. The population in this study was 69 physical education students. The number of samples in the research was 38 students taken by random sampling. Data collection uses an instrument in the form of a questionnaire which has a validity of 0.511 – 0.877 and a reliability value of 0.969. Data analysis uses quantitative description with percentages classified into five categories. The research results showed that 17 students gave very good responses, 13 students gave good responses, 7 students gave responses in the sufficient category, and 1 student gave responses in the poor category. It can be concluded that physical education students responded positively to the implementation of the teaching assistance program in 2023.(Indonesian)Asistensi mengajar memberikan kesempatan kepada mahasiswa untuk mengembangkan potensi maupun minat untuk mengajar di satuan pendidikan di Indonesia. Namun, dalam pelaksanaan di lapangan program asistensi mengajar tidak terlepas dari berbagai hambatan dan berbagai respons dari mahasiswa. Tujuan penelitian ini adalah mengungkapkan respons mahasiswa penjas terhadap program asistensi mengajar pada tahun 2023. Penelitian ini menggunakan metode deskriptif kuantitatif. Populasi dalam penelitian ini berjumlah 69 mahasiswa penjas. Jumlah sampel dalam penelitian adalah berjumlah 38 mahasiswa yang diambil secara random sampling. Pengumpulan data menggunakan instrumen berupa angket yang memiliki validitas sebesar 0,511 – 0, 877 dan nilai reliabilitas sebesar 0,969. Analisis data menggunakan deskriptif kuantitatif dengan persentase yang diklasifikasikan menjadi lima kategori. Hasil penelitian menunjukkan bahwa sebanyak 17 mahasiswa memberikan respons yang sangat baik, 13 mahasiswa memberikan respons yang baik, 7 mahasiswa memberikan repons dengan kategori cukup, 1 mahasiswa memberikan repons dengan kategori kurang. Dapat disimpulkan bahwa mahasiswa pendidikan jasmani memberikan respons yang positif terhadap pelaksanaan program asistensi mengajar pada tahun 2023. Copyright © The Author (s) 2023Journal of Sport Education (JOPE) is licensed under a Creative Commons Attribution-ShareAlike 4.0 International License.